2010
DOI: 10.1590/s1516-635x2010000400005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organic and inorganic selenium on the immune system of growing broilers submitted to immune stimulation and heat stress

Abstract: One to 42-d-old (432) female broilers were fed different levels of inorganic selenium (ISe) and organic selenium (OSe), according to the following treatments: (1) 0.3 mg ISe; (2) 0.3 mg ISe + 0.2 mg OSe; (3) 0.5 mg ISe and (4) 0.3 mg OSe/ kg of feed. All birds were vaccinated against infectious bursal disease (IBD) at 19d of age and three birds/replicate (R) were inoculated with sheep red blood cells (SRBC) at 32d. Three other birds/R received Freund's adjuvant at 37d and avian tuberculin (AT) in the wattle at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…In the present study, the absence of differences may be associated with hen age and constant immunization performed as part of the preventive management; it is also suggested that all treatments covered the needs of hens, and therefore, the effects of Tm were not evident. The CAFQ inclusion also had no effect on haematological parameters, which agrees with what was found by Attia et al, using manganese proteinates in hens age from 30 to 46 weeks and with Silva et al, who used broilers and yeasts as a selenium source. The H:L ratio is a parameter that has been used as a stress indicator; studies carried out with zinc methionine also did not report statistical differences when compared to ITM (Moghaddam & Jahanian, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, the absence of differences may be associated with hen age and constant immunization performed as part of the preventive management; it is also suggested that all treatments covered the needs of hens, and therefore, the effects of Tm were not evident. The CAFQ inclusion also had no effect on haematological parameters, which agrees with what was found by Attia et al, using manganese proteinates in hens age from 30 to 46 weeks and with Silva et al, who used broilers and yeasts as a selenium source. The H:L ratio is a parameter that has been used as a stress indicator; studies carried out with zinc methionine also did not report statistical differences when compared to ITM (Moghaddam & Jahanian, ).…”
Section: Discussionsupporting
confidence: 91%
“…Feng et al, observed some improvements after the use of zinc‐glycine chelates on IgA and IgY levels; similar results were obtained by Moghaddam & Jahanian, with zinc methionine on IgY titres and by Boostani et al, using selenium methionine on IgM. On the other hand, Silva et al, reported that the use of selenium methionine decreased the production of antibodies; they mentioned that the effect of this mineral is more related to tissues integrity and organs and metabolism improvement. Zinc deficiency in young animals has been reported to suppress antibody production due to poor development of the lymphoid tissue in the bursa of Fabricius (Burns, ).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In this study, IgM and IgG concentrations in response to SRBC in groups with nano-Se and organic Se in nonoxidative condition and nano-Se and organic Se increased anti-SRBC antibody. In contrast, Da Silva et al (2010) concluded that usage of organic Se decreased antibody titers against SRBC. The action of this source of Se may be more related to tissue and organ integrity, and to the enhancement of metabolic systems that are key to the organic balance.…”
Section: Discussionmentioning
confidence: 91%
“…Vitamin E provides the first line of defense against oxidative damage, increases lymphoproliferative responses, phagocytic functions and T cell hyper activity [21] and these may be mediated by enhancing the antioxidant activity in the lymphoid tissues [22]. Selenium is an essential nutrient for poultry, which stimulates phagocytosis and chemotaxis of macrophages and neutrophils.…”
mentioning
confidence: 99%